Assessing the Role of Green Finance in Reducing Carbon Emissions: Evidence from Bangladesh - Basher, Shahanara; Chowdhury, Md. Ismail Jubaide; Islam, Md. Towhidul; Hasan, Mohammed Rakibul; Akter, Jane (Asian Business Review, 2025)
Green investment has emerged as a key driver of sustainable economic development globally, and Bangladesh is no exception. This study examines the impact of green finance on carbon emissions in Bangladesh, aiming to determine its contribution to building a greener economy. Using the Autoregressive Distributed Lag (ARDL) bounds testing approach with quarterly data from 2013 to 2023, the findings indicate that green financing has a significant positive impact on air quality by reducing carbon emissions. However, the positive effect of green-oriented foreign direct investment (FDI) on emissions reduction is moderated by overall economic growth, highlighting a tradeoff between growth and sustainability. These results suggest that Bangladesh must strengthen its green financing mechanisms and integrate environmental planning into development policies to ensure a sustainable transition toward a low-carbon economy.